Analisis Struktur Dan Unsur Musik Komposisi Take Five Karya Paul Desmond - Muhammad Irzaq; Esy Maestro (FBS Universitas Negeri Padang, 2021)
This study aims to describe Paul Desmond's Take Five music composition analysis. This type of research is descriptive qualitative research with the main instrument in this study is part music in the form of song parts. The researcher processed the data with steps such as reading the scores from the take five material itself, then classifying the data from understanding music theory to the material itself, from the structural aspect of music to melody, rhythm and interval, so that the researcher can make a summary of the data. which was found in the form of writing describing the understanding of music theory, Then, the researcher conducted a feasibility test on the song with the aim that the song analyzed could be used as learning material for students who studied standard jazz material and as eligibility to be used as basic knowledge about music jazz.The results showed that the work of Take five is unique in terms of odd time signatures using simple melody, riem and intervals, which form a song 2 parts A, B with sentences A (a, a ') B (b, b') and A (a, a ') take five can be accepted as a standard jazz learning reference for the alto saxophone instrument. The assessment is obtained from simple melody, rhythm and interval analysis so that it can be used or can be used as a reference for learning standard jazz for students taking the major saxophone instrument course.